Reflectance spectroscopy in geology and soil sciences: Literature review - Badura, Ireneusz; Dąbski, Maciej (Quaestiones Geographicae, 2022)
This article presents a literature review of studies utilising reflectance spectroscopy in geological research. We describe a variety of available spectral libraries together with providing examples of spectral reflectance diagrams, and explain the basic spectral ranges. Geologists can use different methods of data collection, for example, sensors mounted on satellites, airborne [including unmanned aerial vehicle (UAV) platforms] or portable spectroradiometers, and different ways of data processing. Most geological mapping based on reflectance spectroscopy is performed in the Arctic region, where vegetation does not obscure images. However, mineral mapping, studies of hot spring deposits, and rock/soil weathering alterations are also performed in lower latitudes. The development, combination and unifi-cation of all spectral data acquisition methods open up new possibilities for applications in a variety of geological and soil studies.